Pengaruh Akreditasi Rumah Sakit dalam Mengubah Tingkat Kepatuhan Mengisi Daftar Periksa Keselamatan Bedah di Rumah Sakit Nur Hidayah - Annisa Firdausi; Arlina Dewi; Susanto Susanto (Program Studi Magister Manajemen Rumah Sakit, Jenjang Pasca Sarjana (S2), Pasca Sarjana Universitas Muhammadiyah Yogyakarta, 2019)
Death and complication due to surgeries or surgical actions is a global health problem. The WHO estimates that at least half a million deaths that are caused by surgeries can be prevented. On 2008, the WHO release a campaign about safe surgery and released the surgical safety checklist to improve the quality of our surgery cases and decrease the number of complication and deaths caused by surgeries. Hospital accreditation is used to improve the quality of hospital management, including in reducing numbers of death and complication due to surgeries. This is a quantitative descriptive approach study. The study population used were all surgical safety checklist. Sample number of 75 surgical safety checklist, 15 surgical safety checklist each from June 2017, August 2017, January 2018, June 2018, and January 2019. Data analysis is shown by statistic table and percentage. There was a change of number in completing compliance of the surgical safety checklist before and after hospital accreditation. It showed that nearing hospital accreditation, the compliance rate was almost 100% on all the items. This continued a month after, but some of the items had a lower rate of compliance further after the hospital accreditation. The Conclusion is the number of completing compliance of the surgical safety checklist nearing hospital accreditation is higher than after hospital accreditation. The sign in the item has the highest rate of completing compliance whereas the sign out item had the lowest number of compliance.